2021
DOI: 10.3390/cancers13081901
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Combined with Metronomic Dosing: An Effective Approach for the Treatment of NSCLC

Abstract: Pioneering studies on tumor and immune cell interactions have highlighted immune checkpoint inhibitors (ICIs) as revolutionizing interventions for the management of NSCLC, typically combined with traditional MTD chemotherapies, which usually lead to toxicities and resistance to treatment. Alternatively, MTR chemotherapy is based on the daily low dose administration of chemotherapeutics, preventing tumor growth indirectly by targeting the tumor microenvironment. The effects of MTR administration of an oral prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Informed by prior investigation into immunogenic effects of low dose or metronomic dosing of other chemotherapeutic agents such as cyclophosphamide (Ghiringhelli et al, 2007;Lutsiak et al, 2005;Wada et al, 2009) or oxaliplatin (Shalapour et al, 2015), more recent studies showed that sub-clinical "low" doses of gemcitabine are immunomodulatory in various ways, with effects on NK cell function (Zhang et al, 2020), myeloid polarization (Deshmukh et al, 2018;Di Caro et al, 2016) and Tregs (Homma et al, 2014;Rettig et al, 2011;Shevchenko et al, 2013;Skavatsou et al, 2021;Tongu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Informed by prior investigation into immunogenic effects of low dose or metronomic dosing of other chemotherapeutic agents such as cyclophosphamide (Ghiringhelli et al, 2007;Lutsiak et al, 2005;Wada et al, 2009) or oxaliplatin (Shalapour et al, 2015), more recent studies showed that sub-clinical "low" doses of gemcitabine are immunomodulatory in various ways, with effects on NK cell function (Zhang et al, 2020), myeloid polarization (Deshmukh et al, 2018;Di Caro et al, 2016) and Tregs (Homma et al, 2014;Rettig et al, 2011;Shevchenko et al, 2013;Skavatsou et al, 2021;Tongu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In multiple pre-clinical models, tumor growth in T cell-deficient Nude mice or specific CD8 T cell depletion rendered gemcitabine less effective, suggesting that gemcitabine exhibits T cell-dependent immunogenic activity in addition to direct tumoricidal killing (Suzuki et al, 2007). Informed by prior investigation into immunogenic effects of low dose or metronomic dosing of other chemotherapeutic agents such as cyclophosphamide (Ghiringhelli et al, 2007; Lutsiak et al, 2005; Wada et al, 2009) or oxaliplatin (Shalapour et al, 2015), more recent studies showed that sub-clinical “low” doses of gemcitabine are immunomodulatory in various ways, with effects on NK cell function (Zhang et al, 2020), myeloid polarization (Deshmukh et al, 2018; Di Caro et al, 2016) and Tregs (Homma et al, 2014; Rettig et al, 2011; Shevchenko et al, 2013; Skavatsou et al, 2021; Tongu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is the number one cause of cancer-related deaths worldwide, of which over 80% is identified as non-small cell lung cancer 1 , 2 . Conventional treatments for cancer, like chemotherapy, radiation, or surgery, have numerous side effects for the patient (nausea, hair loss, intestinal dysfunction, skin irritability), entailing risks of drug resistance, collateral damage of healthy tissue, inefficiency against metastasis, and tumor reoccurrence 3 .…”
Section: Introductionmentioning
confidence: 99%
“…As an extension of the peptide-drug conjugate work, another concept, the metronomic approach (MTR) based on the daily low-dose administration of Gem, was recently evaluated[ 33 ]. An oral pro-drug of Gem (OralGem) was chosen for this work in non-small cell lung cancer animal models.…”
Section: Introductionmentioning
confidence: 99%